Mary Edith Powel naval historical collection - Powel, Mary Edith, 1846-1931.
Correspondence, biographical data on American and foreign naval officers, notes, autographs, clippings, commissions, pamphlets, illustrations, and photographs collected by Powel. Newspaper clippings form the bulk of the collection. Subjects include U.S. and foreign navies and naval officers, ships, arms and armor, naval educational institutions, the merchant marine, disasters at sea, marine natural history, Arctic explorations in the 1890s, the World's Columbian Exposition in Chicago in 1893, the Sino-Japanese War, 1894-1895, and the Spanish-American War, 1898. Includes correspondence with Powel's father, Samuel Powel, and other Powel (Powell) family members. Other correspondents include autograph and book dealers, Walter Romeyn Benjamin and M. Bruckner; and naval officers including Stephen Bleecker Luce.
Collector of naval history.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Benjamin, Walter Romeyn, -- 1854-1943 -- Correspondence; Bruckner, M. -- Correspondence; Luce, Stephen Bleecker, -- 1827-1917 -- Correspondence; Powel, Samuel, -- 1818-1885 -- Correspondence; Powell family -- Correspondence; United States. -- Navy -- History; United States. -- Navy -- Officers; Exhibitions -- Illinois -- Chicago; Armor; Marine accidents; Marine biology; Merchant marine; Naval education; Navies; Navies -- Officers; Navies -- Officers -- Autographs; Navies -- Officers -- Correspondence; Ordnance; Ships; Sino-Japanese War, 1894-1895.; Spanish-American War, 1898.; Arctic regions -- Discovery and exploration; United States -- History, Naval; Collectors